A prospective, randomized, double blind, placebo controlled clinical trial to study efficacy and safety of benzydamine 0.15% gargles in prevention of postoperative sore throat - Gaikwad, Smita M.; Rupwate, Kanchan R.; Tendolkar, Bharati A. (International Journal of Research in Medical Sciences, 2017)
Background: Postoperative sore throat (POST) is an undesirable outcome of general anesthesia. The aim of the study was to evaluate the effectiveness of benzydamine preoperative gargles in reducing the incidence and severity of POST. Methods: A randomized double blind prospective study involving 200 adult male and female patients was performed to assess the incidence of sore throat, cough and hoarseness of voice following tracheal intubation. The patients were randomly divided into two groups (group B and group C) of 100 each. Group B patients received benzydamine 0.15% gargles while group C received placebo. Patients were asked to gargle for 30 seconds, five minutes before induction of anesthesia. The patients were examined for sore throat, cough and hoarseness of voice at intervals of 0, 2, 4, and 24 hours post-extubation. Results: The incidence of POST was significantly high (p<0.05) in the group C (controls) as compared to group B (cases) at all the durations of time after extubation. The peak incidence was noted at 0 and 2 hours post extubation, in both the groups, where 89% in group C and 47% reports of sore throat in group B were observed. The benzydamine group B had no evidence of sore throat at 24 hours duration whereas group C had 36% of patients who still complained sore throat. The incidence and severity of hoarseness of voice was found to be significantly low in group B at all the times as compared to group C (p<0.05). Conclusions: A simple technique of gargling performed preoperatively with benzydamine hydrochloride was effective in reducing POST with no evidence of any side effects.